Timothy Dodd House on North Street, ca. 1888 - Unknown (Tufts Archival Research Center, 2005)
Street-level view east-northeast of the Timothy Dodd House, located at the northeast corner of North Street and Smith Place. The facade of the house faces west. The southwest corner of the Tremere House is visible to the left of the Dodd House. Other buildings are included in the photograph, including those lining the north side of Smith Place. A street lamp is located at the southeast corner of North Street and Smith Place. Dodd House demolished, 1889 4 1/2 x 7 3/4, 8 x 10 overall Albumen prints